Peningkatan Budaya Literasi dan Numerasi Melalui Kegiatan Festival Literasi dan Numerasi di Kota Lubuk Linggau - Rizki, Fido; Nopalia, Nopalia (Pusat Riset dan Inovasi Nasional, 2024)
The decline in the culture of literacy and numeracy in Lubuk Linggau City has resulted in low interest in reading among the public, especially students, as well as a lack of adequate facilities and infrastructure to support these activities. To coincide with the commemoration of National Education Day, a literacy and numeracy festival at elementary, middle and high school levels was held. The aim is to arouse students' interest in improving the culture of literacy and numeracy, the method used in this activity is holding several competitions, the aim of holding the competition is to increase students' enthusiasm in competing to improve the culture of literacy and numeracy. The results obtained from this activity are very beneficial for the community, especially students, with this literacy and numeracy festival, students can develop and improve literacy and numeracy culture for the advancement of education in Lubuk Linggau City..